الصيرفة الإسلامية في دولة قطر : دراسة فقهية تقويمية دراسة فقهية تقويمية - شمري، نايف بن نهار (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Using the analytical, critical and comparative methods, this study touches on the issue of Islamic banking in Qatar from an evaluative critical perspective, and it commences by mentioning the historical background of banking in general and Islamic banking specifically, as well as some of the effective rules in the functioning of Islamic banking. In the second chapter the study examines the legislation of Qatar Central Bank in relation to the structuring of Shari'ah compliance bodies, while revealing the effect of those legislations on the reality of Islamic banking in Qatar. The study alsoidentifies the tools of monetary policy imposed upon Islamic banks by Qatar Central Bank, which in return affects the processes of banking through creating dilemmas relating to Shari'ah compliance and economy. The researcher ends this chapter by mentioning some alternative suggestions to monetary policy. The next chapter deals with tawarruq banking by firstly defining it, then mentioning the differences in Islamic jurisprudence regarding individual tawarruq and organised tawarruq. The researcher then expressed his view towards tawarruq in terms of its essence and in terms of what is actually implemented by Qatari Islamic banks. The study also discusses the issue of lease contract that ends in ownership attached to fluctuating index. At the beginning it looks into the Islamic ruling regarding lease contracts that end in ownership. In the final chapter, the researcher looks into two banking services, which are debit cards and letters of guarantee from the perspective of Islamic jurisprudence. They are both firstly dealt with from the viewpoint of Islamic jurisprudence and then discussed as two banking services implemented by Qatari Islamic banks. The study found that some Islamic banks in Qatar do not work according to the law and Shari'ah.